Architectural And Cultural Heritage Tourism Products In Nepal : An Assessment of New Private Sector Investment Opportunities in the Tourism Sector in Annapurna Conservation Area - International Finance Corporation (Washington, DC, 2022)
IFC supports the tourism industry because of its strong development impact. It is easily accessible to rural entrepreneurs, allows for local approaches and products, has a bias towards female participation, and enables excellent supply-chain linkages. Our activities in tourism are aimed at promoting private sector-investments leading to sustainable and inclusive growth. In Nepal, tourism development also enables the creation of cultural, adventure, and sightseeing experiences that have appeal and significance among its established global, loyal market of visitors—ranging from pilgrims to mountaineers, hikers, and wellness and sightseeing travelers. But the COVID-19 pandemic has hit the tourism industry especially hard. The potential loss to the country’s GDP from the collapse of tourism activities is estimated at $460 million. Around 230,000 jobs are at risk; 20,000 tour and trekking guides are unemployed, and 2,600 trekking agencies are closed, some maybe permanently. Now, as outbound markets begin to show signs of recovery, it is time to implement strategic adjustments to Nepal’s tourism sector and implement policies that will align the destination with the new market reality.